2022
DOI: 10.1530/joe-21-0393
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone/bupropion modifies weight, food intake, and Drd2 gene expression in rats

Abstract: Obesogenic diets are known to induce obesity and changes in food intake in experimental animals. Obesity negatively affects the peripheral metabolism and neural aspects, such as changes in eating behavior. In obese animals, dopamine (DA) receptor levels are reduced. Dopamine is one of the main peptides involved in the motivation and pleasure of eating. A combination of naltrexone/bupropion (NB) has shown promise in controlling metabolic alterations, but there are few studies on how they modulate dopaminergic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent research has shown that the combination of naltrexone and bupropion may effectively control metabolic changes. Other studies suggest that this drug combination modulates dopaminergic expression [ 73 ]. Based on the safety and clinical efficacy analysis of drugs for treating obesity, bupropion is on the list of drugs that can effectively reduce body weight [ 74 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%
“…Recent research has shown that the combination of naltrexone and bupropion may effectively control metabolic changes. Other studies suggest that this drug combination modulates dopaminergic expression [ 73 ]. Based on the safety and clinical efficacy analysis of drugs for treating obesity, bupropion is on the list of drugs that can effectively reduce body weight [ 74 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%